Identitas Gender dalam Praktik Crossdressing di Komunitas Dance Cover K-Pop Kota Banjarmasin - Aziza, Wafiq; Hidayah, Sri (Huma: Jurnal Sosiologi, 2025)
In the K-Pop dance cover community in Banjarmasin City, some male crossdressers present performances imitating original K-Pop groups, including showcasing costumes and expressions that match the gender of the idols they imitate. The aim of this research is to highlight how their identities are formed and lived, both on stage and in everyday life. This study employs a qualitative method with a phenomenological approach. Data collection was carried out through observation, in-depth interviews, and documentation. Data analysis uses methods that include Data Collection, Data Reduction, Data Presentation, and Conclusion. The results of the study indicate that being a crossdresser is not merely a role played for performance needs, but has become a real part of the identity lived in everyday life. The crossdressers show involvement in their way of dressing, speaking, and social interactions outside of performance contexts. The researcher reveals that the gender expressions displayed by crossdressers are the result of a process of repetitive actions that gradually shape identity, demonstrating that gender performance does not only occur within a Western discursive context but can also root and transform within local community spaces rich in collective values, religion, and social ethics. Academically, this study contributes to the development of gender studies, particularly within the context of non-urban performing arts communities that are still rarely researched. Theoretically, this research enriches Butler's theory of performativity by showing how gender performance can grow and transform within local communities.